THE STUDY OF SPEECH ETIQUETTE AS A SUBJECT OF LINGUISTIC AND CULTURAL ANALYSIS - Qobulova Guzal Qilichevna (Scholar Express Journal, 2024)
The ecology of linguistics reveals one of the most important problems of modern language and speech, the lack of etiquette, which significantly increases the status of such a concept as speech culture, because the rules of etiquette are its mandatory component.
Keywords: Etiquette; Communicative Stereotype; Manners